A negative association between total cholesterol and bone mineral density in US adult women - Fang, Weihua; Peng, Peng; Xiao, Fangjun; He, Wei; Wei, Qiushi; He, Mincong (Frontiers in Nutrition, 2022)
Abstract Background: The association between serum total cholesterol (TC) and bone mineral density (BMD) is still controversial. We aimed to evaluate the association of serum TC with BMD in general US adult women. Methods: A cross-sectional study consisting of 7,092 (age range 20-85) participants from the National Health and Nutrition Examination Survey (NHANES) database was conducted. Weighted multivariate linear regression analyses were performed to evaluate association between serum TC and lumbar spine BMD. In addition, subgroup and interaction analysis were used in this study. Results: The serum TC was negatively correlated with lumbar spine BMD after adjusting for confounders. Subgroup analysis found that the strongest negative association mainly exists in women aged over 45 years with body mass index (BMI) less than 24.9 kg/m2, and this association is not significant in other groups. Conclusions: This study found that serum TC exhibit an inverse association with lumbar spine BMD in Us women aged over 45 years. The measurement of serum TC may provide information for predicting poor bone health outcomes in these women.